2017
DOI: 10.3390/ijms18030531
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of HK-2 Cells as a Relevant Model to Study Tenofovir-Induced Cytotoxicity

Abstract: Tenofovir (TFV) is an antiviral drug approved for treating Human Immunodeficiency Virus (HIV) and Hepatitis B. TFV is administered orally as the prodrug tenofovir disoproxil fumarate (TDF) which then is deesterified to the active drug TFV. TFV induces nephrotoxicity characterized by renal failure and Fanconi Syndrome. The mechanism of this toxicity remains unknown due to limited experimental models. This study investigated the cellular mechanism of cytotoxicity using a human renal proximal tubular epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Our findings are supported by a recent report by Murphy et al 30 These authors have investigated the cellular mechanism of TDF cytotoxicity using a human renal proximal tubular epithelial cell line (HK-2).They have demonstrated that incubation of HK-2 cells with different concentrations of TDF resulted in decreased cell viability, increased oxidative stress biomarkers–protein carbonylation and 4-hydroxynonenol, mitochondrial dysfunction and increased expression of cleaved caspases 3 and 9. These authors have suggested that TDF induces apoptosis in HK-2 cells and that mitochondrial dysfunction may be a major contributing factor to loss of cell viability.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are supported by a recent report by Murphy et al 30 These authors have investigated the cellular mechanism of TDF cytotoxicity using a human renal proximal tubular epithelial cell line (HK-2).They have demonstrated that incubation of HK-2 cells with different concentrations of TDF resulted in decreased cell viability, increased oxidative stress biomarkers–protein carbonylation and 4-hydroxynonenol, mitochondrial dysfunction and increased expression of cleaved caspases 3 and 9. These authors have suggested that TDF induces apoptosis in HK-2 cells and that mitochondrial dysfunction may be a major contributing factor to loss of cell viability.…”
Section: Discussionsupporting
confidence: 90%
“…We found that gentamicin has a higher toxicity to HK‐2 than HEK‐293, which was expected since the proximal tubule cells are more sensitive to aminoglycosides, such as gentamicin. This effect was also observed in other studies, even for animal strains such as proximal and distal convoluted tubulus LLC‐PK1 and MDCK, respectively …”
Section: Resultssupporting
confidence: 86%
“…Therefore, proximal convoluted tubules are the main toxic target cells of inorganic mercury. The HK-2 cells, which are immortalized human renal cortex proximal convoluted tubule epithelial cells, have various characteristics of normal cortical juxta convoluted tubule epithelial cells, and are often used as an effective model for the study of mercury nephrotoxicity in vitro [ 33 , 34 ]. Therefore, the Hk-2 cells were employed in the present study as well.…”
Section: Discussionmentioning
confidence: 99%